0649 Tasimelteon Improves Number of Sleep Free Days in Blind Patients with Non-24-Hour Sleep-Wake Disorder. (27th April 2018) - Van Draanen, L; Xiao, C; Polymeropoulos, M H
Abstract: Introduction: Non-24-Hour Sleep-Wake Disorder (Non-24) is a circadian rhythm disorder with a significant impact on social and occupational functioning. Utilizing longitudinal sleep diary data, we have previously shown significant decrease in the number of healthy days through the measurement of Daytime sleep Free Days (DSFD) in untreated patients with Non-24. Daytime sleep episodes may interfere with schoolwork and social activities and we have now studied the effect on DSFD in Non-24 patients entrained by tasimelteon. Methods: Daytime sleep diary data of patients who were treated with tasimelteon and showed entrainment of circadian rhythm, were collected and analyzed from the SET and RESET studies. Data collection extended to approximately 7 months, and DSFD was calculated in 30-day units. DSFD analysis was performed by a paired t test. Results: Tasimelteon entrained the circadian rhythm in 59% of blind patients by month seven. In a categorical analysis, patients slept at least 1 hour or more during the daytime on 19 out of 30 days at baseline, compared with 13 out of 30 days after entrainment with tasimelteon (pvalue 0.008). Patients entrained after treatment with tasimelteon had significantly more DSFD in a 30-day period than they did at baseline. Conclusion: DSFD is a useful measure of disease burden in patients with Non-24-Hour Sleep-Wake Disorder. Tasimelteon significantly improves the number of Healthy Days measure by DSFD in entrained patients with Non-24. Support (If Any): This work was supported by Vanda Pharmaceuticals Inc.